Poly-phenylenediamine-derived atomically dispersed Ni sites for the electroreduction of CO2 to CO. Issue 7 (24th May 2019) - Zheng, Yonglong; Han, Jianyu; Takele, Leta; Xie, Feng; Zhang, Yin; Sun, Jiqing; Han, Bing; Chen, Jing; Gao, Yan; Tang, Zhiyong
Abstract : A highly efficient atomically dispersed Ni catalyst for CO2 electroreduction was synthesized by a simple and low-cost method. Abstract : CO2 electroreduction is a promising technique for the management of the global carbon balance by low-grade renewable electricity. However, the lack of highly efficient and selective catalysts has hampered the development of this area. Herein, we report a poly-phenylenediamine-derived atomically dispersed Ni catalyst as a highly efficient and selective electrocatalyst for the conversion of CO2 to CO. The catalyst facilitates efficient production of CO with high faradaic efficiency (FE) (90%) and a large current density of 11.6 mA cm −2 at −0.8 V compared to a reversible hydrogen electrode (RHE). An excellent turnover frequency (TOF) of 3079 h −1 for the electroreduction of CO2 was also achieved at −0.8 V vs. RHE.